Analisis Perbandingan Syarat Kualitatif Anggota Majelis Syuro dengan Kriteria Pemilih dalam Sistem Pemilihan Umum Presiden di Indonesia - Ahmad Sadzali (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2023)
This paper conducted a comparative study between the qualitative requirements for members of the Syuro Council in Islamic Constitutional Law (Siyasah) and the voter qualifications in the presidential election system in Indonesia. This comparative study is normative research with a literature review. As a result, voter qualifications in general elections in Indonesia have only reached qualifications that are externally administrative in nature and tend to be formal. When compared with the formulation of qualitative-substantive requirements set by Imam Al-Mawardi, voter qualifications in Indonesia still do not reach the qualification aspects of integrity, intellectual capacity, or rhetorical capacity.